2007
DOI: 10.1093/pubmed/fdm043
|View full text |Cite
|
Sign up to set email alerts
|

General practitioner notifications of gastroenteritis and food poisoning: cause for concern

Abstract: We suggest that the current notification system is not working in respect of gastroenteritis and food poisoning, and should be either substantially revised or abandoned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…This will serve as a guide to the food providers to apply nutrition principles that will promote the nutritional status of the consumers. 4. The fast foods providers should be taught food selection and safe food storage.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will serve as a guide to the food providers to apply nutrition principles that will promote the nutritional status of the consumers. 4. The fast foods providers should be taught food selection and safe food storage.…”
Section: Recommendationsmentioning
confidence: 99%
“…Hygiene is the maintenance of health and healthy living. It is a science that deals with the promotion and prevention ill-health [4]. Hygiene deals with the sanitary science which aims at producing food which is safe for consumption and of good keeping quality [12].…”
Section: Introductionmentioning
confidence: 99%
“…In locations where reporting is mandatory, it has been found that actual notification is poor with a trend even declining [Day 2007]. Such practices do not allow the full realization of disease rate and can perpetuate an endemic event.…”
Section: Communicable Diseasesmentioning
confidence: 99%
“…Such practices do not allow the full realization of disease rate and can perpetuate an endemic event. This becomes even more important with the finding that there are 200 cases of gastrointestinal disease for every 1,000 registered patients a year in England [Day 2007]. However, the delay in laboratory reporting sometimes can be considerable.…”
Section: Communicable Diseasesmentioning
confidence: 99%
See 1 more Smart Citation